(3EYQGH GdbQBfs - (3GdRLGL , EHQGgje Hf GdSQj Hf Sgd, CHhESMGb,J (B311 (3g` s
(3ChdgG (B:s
(3bhdg (B: " (3jG CjgG GdfHi EPG LGAc GdeDefGJ jHGjYfc Ydi GdG jTQcf HGddg TjFkG (B" (3ef ShQI GdeeJMfI s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B:" (3hbhdg (B:" (3ef GdLfI hGdfGS (B" (3bjd (B: (3GdfGS gGgfG jUdi ddLf hGdEfS GdeYfi Ydi gPG s
(3SbW GdLRA GdKGdK hGdNeShfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B40 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B33s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , HgG NQe s
(3GdfSNI HgG JdhjK s
Keywords: (3GdfMhs